2020
DOI: 10.3390/molecules25204606
|View full text |Cite
|
Sign up to set email alerts
|

Significance of Targeting VEGFR-2 and Cyclin D1 in Luminal-A Breast Cancer

Abstract: The hormonal luminal-A is the most pre-dominant sub type of breast cancer (BC), and it is associated with a high level of cyclin D1 in Saudi patients. Tamoxifen is the golden therapy for hormonal BC, but resistance of cancer cells to tamoxifen contributes to the recurrence of BC due to many reasons, including high levels of AIB1 and cyclin D1. Overcoming drug resistance could be achieved by exploring alternative targetable therapeutic pathways and new drugs or combinations. The objective of this study was to d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 53 publications
(75 reference statements)
0
9
0
Order By: Relevance
“…The PamChip ® peptide microarray-based kinase activity profiling assays were done as previously described [ 32 ]. The immobilized peptides in the PamChip ® micro-arrays can be phosphorylated by the kinases present in the investigated sample(s) in the presence of ATP.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The PamChip ® peptide microarray-based kinase activity profiling assays were done as previously described [ 32 ]. The immobilized peptides in the PamChip ® micro-arrays can be phosphorylated by the kinases present in the investigated sample(s) in the presence of ATP.…”
Section: Methodsmentioning
confidence: 99%
“…The immunofluorescence staining was used to test the effect of the compounds on EGFR and caspase 8 in HT29 cells, p27 and p21 in HT29-5FU cells according to a previous report [ 32 ]. Cells (2 × 10 5 /chamber) were incubated (72h) with vehicle, 5FU (0.25 µM), HAA 2020 (3 µM), or their combination.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…To investigate the ability of compound 16g to induce apoptosis, MCF7 cells were treated with three different concentrations (0.01, 0.05, and 0.10 μM) of the test compound following the previous report [ 37 ]. The results showed that compound 16g induced a dose-dependent increase in the apoptotic events in MCF7 cells compared to the control group (from 7.9–17.8%), Figure 13 .…”
Section: Resultsmentioning
confidence: 99%
“…MCF7 cells were treated by compound 16g at 0.00, 0.01, 0.05 and 0.10 μM final concentrations for 72 h. Briefly, the superanent of the cells was collected in ice-cold tubes, trypsinized and incubated (37 °C). The procedures were completed following the previous report [ 37 ]. The samples were analyzed using flow cytometry (BC, FC500, Brea, CA, USA).…”
Section: Methodsmentioning
confidence: 99%